Determinación del Costo de Producción de Café en la Asociación de Producción Cafetalera del Sur Oriente de la Provincia de Loja “PROCAFEQ”, durante el período octubre-diciembre del 2021 - Gaona Cruz, Dayanara Berenice (2022)
The Curriculum Integration Work named DETERMINATION OF THE COST OF COFFEE PRODUCTION AT THE COFFEE PRODUCTION ASSOCIATION OF THE SOUTHEAST OF THE PROVINCE OF LOJA "PROCAFEQ", DURING THE PERIOD OCTOBER-DECEMBER 2021, was carried out to provide a useful tool to determine the unit cost involved in the production of coffee for the aforementioned association. In order to establish the cost of coffee production, the system of costs by production orders was used to identify the behavior of the of the elements of cost. In the development of the work, the following was carried out, the initial inventory was assessed by means of the physical verification of the goods, rights and obligations of the entity; in addition, the Plan and Manual of coded and ordered Accounts was elaborated according to its economic activity, serving as a guide for the elaboration of the Statement of Initial Situation. Furthermore, the auxiliary formats for the control of the different elements of the cost, such as production orders, material requisition orders, Kárdex cards, clock and time cards, work spreadsheets, payrolls and supply lists, cost sheets, among others. For the accounting record of the activities carried out, the accounting entries were made in the Daily Book, taking as a reference the control of the cost elements in their corresponding formats for raw materials, labor and indirect production costs, the addition to the General Ledger for the preparation of the Balance Sheet and the Worksheet with the respective adjustments, allowing to obtain the Financial Statements, which present the following values as of December 31, 2021: Revenues $299,925.50; Costs 208,740.39; Expenses $9,269.91; Profit of $81.915,20; Assets of $477,026.26; Liabilities of $11.411,83; Net Worth of $465.613,43 and a net cash flow of $295.843,65. As for the determination of the balance point, the classification of the fixed and variable costs of the results were done. These were reflected in the Income Statement to learn the minimum number of sales with which the costs involved are covered in order to generate profits during the period. Thus, it was determined that for the production of roasted coffee to be profitable, sales must be equal or greater than $217.94; for roasted ground coffee $118.89; for parchment coffee $73.65; and lastly, for organic parchment coffee of $30,680.35. In light of the information provided during the accounting process, a unit cost of $2.34 was obtained for roasted coffee, 3.05 for roasted ground coffee, $121.85 for organic parchment coffee and $111.97 for parchment coffee; likewise, a unit price of $2.68 for roasted coffee, $4.44 for ground roasted coffee, $175.00 for organic parchment coffee, and $192.00 for parchment coffee. Subsequently, once the work in the determination of the coffee cost production was completed, the elaboration of the conclusions and recommendations was carried out, which constitute a contribution to the development and growth of the Association; and consequently, will serve as a tool that will enable them to take informed decisions and therefore grow as an Association